Corporate board and sustainability reporting in Malaysia - Mohd Ghazali, Nazli Anum; Ahmad, Maslina; Sheikh Abu Bakar, Aishah (2019)
This study examines the extent and quality of sustainability reporting after the introduction of the Sustainability Reporting Framework by Bursa Malaysia in 2015. Content analysis was performed on 98 company annual reports using a checklist comprising 90 indicators. The research also investigates whether board diversity has an impact on sustainability reporting. Multiple regression analyses employing twelve independent variables were run using data from annual reports for financial year ended on or after 31 December 2016. The results show a mean score of 40.7% for extent of disclosure and 31.6% for quality of disclosure. The paired sample t test result shows the extent and quality of sustainability reporting is significantly different at the 1% level suggesting that on average companies tend to disclose information without much elaboration. Ethnic diversity, Malay, Indian, foreign and female directors were found to have significant influence on sustainability reporting. These findings provide some evidence on the importance of board diversity in further enhancing corporate sustainability agenda.